Real-Time Monitoring of Electrochromic Memory Loss of Layered α-MoO3Nanoplates - Felix, A. A. [UNESP]; Barbosa, M. S. [UNESP]; Bueno, P. R. [UNESP]; Orlandi, M. O. [UNESP] (The Electrochemical Society, 2020)
Combined in situ cyclic electrochemical and UV-vis spectroscopic methods were employed to monitor the memory loss of electrochromic properties of layered α-MoO3 nanoplates. The time-resolved characteristics of this in situ study allowed for the quantification of changes in charge and optical densities as a function of electrochemical potential over time. Lithium ions trapped in the crystalline lattice of α-MoO3 during the bleaching process, along with the irreversible reduction of Mo6+ to Mo5+, govern the memory loss responsible for the degradation of the electrochromic properties. These experiments demonstrated the existence of a saturation limit of the structural charge insertion that effectively contributes to the electrochromic performance of α-MoO3 nanoplates. The study improves the understanding of electrochromic memory loss and the degradation mechanism and suggests a two-step electrochemical reaction that controls the electrochromic activity of the α-MoO3 phase.